High flux polysulfone braided hollow fiber membrane for wastewater treatment role of zinc oxide as hydrophilic enhancer. Issue 5 (October 2021) - Peechmani, Prakash; Othman, Mohd Hafiz Dzarfan; Kamaludin, Roziana; Puteh, Mohd Hafiz; Jaafar, Juhana; Rahman, Mukhlis A.; Ismail, Ahmad Fauzi; Kadir, Siti Hamimah Sheikh Abdul; Illias, Rosli Md.; Gallagher, Joe; Djuli, Sabreenna Marsya
Abstract: Incorporation of zinc oxide (ZnO) nanoparticles has played an important role on the improvement of unique membrane characterization and performance, most notably the hydrophilic modification of the membrane for higher pure water permeability. Additionally, the permeability of the membrane can be improved via introduction of braid support by reducing the thickness of the membrane separation layer. Moreover, the braided hollow fiber membrane (BHFM) is able to perform under higher pressure conditions compared to hollow fiber membranes. In this paper, hybrid polysulfone (PSf)/ZnO BHFMs were fabricated via phase inversion method. Hydrophilic 10 ± 1.8 nm polycrystalline ZnO nanoparticles synthesized via sol-gel method were incorporated on BHFM to improve the hydrophilicity and increase flux with constant rejection under high pressure and the effect of the ZnO loading on the membrane properties and performance were thoroughly studied. The fabricated BHFMs with 0.0, 0.5, 1.0 and 1.5 wt% of ZnO nanoparticles concentration were defined as BHFM1, BHFM2, BHFM3 and BHFM4 respectively. Scanning electron microscopy (SEM), contact angle, mechanical strength, flux performance, rejection with bovine serum albumin (BSA) and fouling of best performed membrane were conducted to achieve the target of this paper. The performance of these hybrid ZnO/PSf BHFMs were compared with neat PSf hollow fiber membrane (HFM) and previous studies. The findings from this research work shows that BHFM4 has the most desired properties for wastewater treatment application. The ZnO nanoparticles in BHFM4 have improved hydrophilicity from 108.79° to 71.02°, and thus BHFM4 has increased flux performance from 36.20 to 919.12 L/m 2 h at 1.0 bar pressure and 193.48 to 1909.11 L/m 2 h at 4.0 bar pressure when compared with BHFM1. Constant BSA rejection rates (> 90%) were observed in all BHFMs. The improved hydrophilicity and pure flux performance with constant rejection rate in high pressure conditions illustrates the suitability of fabricated ZnO/PSf BHFMs in wastewater treatment applications. Graphical Abstract: ga1